Refraiming the aid debate: Why aid isn't working and how it should be changed - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2009)
Everyone knows that aid is not working as intended, and that something must change. The big question is how to change the status quo. The current international aid debate is characterized by dichotomies and over-simplified generalizations. In order to push the debate forward and identify solutions we must first reframe the aid debate. The most important factors undermining aid's effectiveness need to retake center stage in the debate. These include: what is economic development and the role of aid in achieving it; the politics of aid relationships in aid dependent countries and have they generate perverse incentives; and the everyday practices and bureaucratic routines of aid agencies and how they diminish the impact of aid. Based on a reassessment of why aid is working, and on assessment that reforms inspired by the Paris Declaration have largely failed, the paper concludes with a different approach to changing the way donor countries think about aid and the way bilateral and multilateral agencies give aid.
Keywords: 330; Entwicklungshilfe; Entwicklungsorganisation; Entwicklung; Entwicklungsstrategie; Geberländer